Forecasting using predictive likelihood model averaging - George Kapetanios; Vincent Labhard; Simon Price (Queen Mary University of London, Department of Economics, 2006)
Recently, there has been increasing interest in forecasting methods that utilise large datasets. We explore the possibility of forecasting with model averaging using the out-of-sample forecasting performance of various models in a frequentist setting, using the predictive likelihood. We apply our method to forecasting UK inflation and find that the new method performs well; in some respects it outperforms other averaging methods.
Keywords: C11; C15; C53; 330; Forecasting; Inflation; Bayesian model averaging; Akaike criterion; Forecast combining